Producing policy relevant systematic reviews: navigating the policy-research interface. (1st June 2018) - Oliver, Sandra; Bangpan, Mukdarut; Dickson, Kelly
Abstract : This study employed insider research and reflective practice to investigate exchanges across the research-policy interface to understand the practice of producing policy-relevant systematic reviews. Interviewees came from 11 systematic reviews or review programmes which spanned four models of policy-relevant reviews and between them provided evidence for understanding policy problems, comparing policy options, or implementing policy decisions. No review methodology was found to be uniquely appropriate for policy-relevant systematic reviews. It was the mutual engagement across the research-policy interface that made the reviews policy-relevant. This involved thinking about the issues and seeing them from multiple viewpoints to identify and shape questions; this prompted implicit or explicit value-driven debates. The intellectual work to shape a policy-relevant systematic review is an iterative, collective endeavour that requires partners from either side of the policy-research interface to engage with the unfamiliar, listen, challenge and co-construct questions and answers. Key messages Policy relevant systematic reviews are shaped by: Horizon scanning, consulting or setting research agendas with policy makers; Postgraduate students combining research training with employment backgrounds in policy; Knowledge brokering between worlds of policy and research; and/or Lateral thinking, exploratory thoughtprovoking discussion and constructive conflict.